EXPERIMENTAL AND NUMERICAL SIMULATION OF A NOVEL MAGNETIC POLE REPULSIVE PASSIVE DAMPER FOR VIBRATION CONTROL (Advances in Civil and Architectural Engineering, 2023)
This article presents a novel magnetic pole repulsive damper (MPRD) incorporating neodymium magnetic repulsive blocks and springs. The study explores the mechanical properties of the springs and magnetic blocks through numerical simulations using ANSYS and experimental evaluation. To gain deeper insights into the behaviour of the MPRD, an accurate and high-fidelity finite element model was developed. The evaluation process involved a comprehensive comparison between the numerical simulations and experimental tests, explicitly focusing on cyclic compression–tension forces. The study encompassed the functioning, design implications, fabrication technique, mechanical performance, and numerical simulation for the cyclic compression–tension forces of the MPRD. The cyclic compression–tension tests revealed a gradual increase in force, with the MPRD achieving an ultimate force of 2,877 kN. The MPRD exhibited robust hysteresis behaviour in cyclic loading, showing its capacity to undergo and uphold the stability of the combination of its materials. The cyclic compression–tension results indicated the maximum force carrying capability of the damper. This resilience implies its full reusability in such scenarios. The comparison between cyclic compression–tension tests confirmed the alignment between the numerical simulation and experimental investigation.